Analisis Persepsi Masyarakat dan Pelaku Usaha terhadap Strategi Pengembangan Kawasan Halal dalam Mendukung Pertumbuhan Ekonomi Syariah 5.0 di Indonesia - Chasna Noer Setyani; Nur Milla; Adinda Rifantini; Muhammad Ersya Faraby (SiNORA, 2025)
The transformation toward Islamic Economy 5.0 requires synergy among spiritual values, technological innovation, and inclusive policy to develop a globally competitive halal ecosystem. This study aims to analyze public and business actors’ perceptions of halal zone development strategies as a driver of sustainable Islamic economic growth in Indonesia. A descriptive qualitative approach was employed through in-depth interviews and strategic literature review. Data were analyzed using the Miles and Huberman interactive model, consisting of data reduction, display, and conclusion drawing. The findings reveal that the public holds a predominantly positive perception of halal zones, viewing them as instruments of halal assurance, supply chain transparency, and socio-economic empowerment. Business actors, particularly MSMEs, regard halal zones as strategic opportunities for market expansion and brand credibility, although challenges remain in certification costs and procedural complexity. The study concludes that the effectiveness of halal zone development depends on digitalized halal certification, technology-driven MSME empowerment, and Quadruple Helix collaboration among government, academia, businesses, and communities. The key implication suggests that the integration of positive perception, digital innovation, and sharia-based governance acts as a catalyst for realizing an inclusive and sustainable Islamic Economy 5.0.